(untitled) (Iraqi Journal of Market Research and Consumer Protection, 2026)
The mixture of Fe2O3 Nanoparticles prepared from Serratia fonticola with glyphosate herbicide were exposed against weeds (Bermuda) during the field experiment. A total of 42 soil samples were collected from various agricultural areas in Baghdad city, five species of bacteria that grew the most were selected for regarding other isolates: Enterobacter cloacae complex, Serratia fonticola, Aeromonas hydrophila, Pantoea spp. and Pseudomonas mendocina. Extracellular extracts of these bacteria were made and then used to manufacture iron oxide nanoparticles biologically. It was observed after measuring the average diameter by Atomic Force Microscopy (AFM) for each nanoparticles prepared from these bacteria were 65.14, 29.21, 63.87, 57.89 and 36.59 nm, respectively. Additionally, the synthesis conditions were precisely taken into consideration a pH of 7 and a temperature of 50°C. Based on the AFM values, Serratia fonticola was selected as having the smallest average diameter of 29.21 nm to complete the rest of the techniques, such as:- UV-VIS, FE-SEM and AFM. The wavelength of biosynthesis of Fe2O3 NPs is 378 nm, Image of Fe2O3 NPs displays spherical form and the average volume is 29.21 nm, respectively. Three concentrations of the prepared Iron Oxide Nanoparticles (Fe2O3 NPs) from Serratia fonticola were 0.5, 1 and 1.5 g/ml which mixed with Glyphosate herbicide that according to the concentration recommended by the manufacturer and used against Bermuda grass in a controlled experimental environment. The best treatment was the 5 treatment was concentration of Fe2O3 NPs 1.5 g/ml with Glyphosate showed a significant impact on the growth and health of Bermuda grass during 7 days, it was shortest period of synergistic effects with the Glyphosate, influencing the color of grass, change, wilting, and growth cessation. Controlling Cynodon Dactylon L. (Bermuda weed) using Glyphosate herbicide and varying concentrations of Fe2O3NPs and choose the treatment that combined 1.5g/ml of Fe2O3 NPs with glyphosate had the highest control percentage 90% against Bermuda weed.